A systematic review on resource provisioning in fog computing. Issue 4 (27th January 2023) - Kaur, Kirandeep; Singh, Arjan; Sharma, Anju
Abstract: Resource provisioning is allocating resources to clients over the Internet and plays a prominent role in cloud computing infrastructure‐as‐a‐service (IaaS). The main issues of resource provisioning are meeting user demands like bandwidth, response time, throughput, availability, and so on. The cloud computing framework uses virtualization technology to provide on‐demand access to computer system resources, specifically computation and storage. In cloud computing, computing resources are shared across another communication network using virtualization. However, the cloud computing mechanism cannot meet the needs of a large number of Internet of Things (IoT) services. To consider this, fog computing was introduced as a modified mechanism of the cloud paradigm by providing cloud services for the end devices. Fog computing is a decentralized computing model placed between devices, edges, data centers or the cloud. In this way, it helps to meet the demands initiated by IoT services, such as reduced latency, wide mobility coverage, and so on. Several solutions regarding resource allocation in fog computing are available in the research field, but such solutions have not achieved satisfactory results. Therefore, finding a solution by analyzing recent problems is open research. Therefore, this paper reviews different methods established for resource provisioning in fog computing using different parameters from 2015 to 2021 and introduces the limitations, advantages and future directions related to different resource provisioning techniques. Abstract : The cloud computing framework uses virtualization technology to provide on‐demand access to computer system resources, mainly computation and storage. In cloud computing, the computing resources are shared over a different communication network with the help of virtualization. However, the cloud computing mechanism cannot fulfill the requirements of several IoT services. To consider this, Fog computing has been introduced as a modified mechanism to the cloud paradigm by providing cloud services to the end devices. Fog computing is a decentralized computing model placed in the middle of devices, edges, data centers, or the cloud. Thus, it assists in obtaining the requirements initiated by IoT services like reduced latency, large mobility coverage, and so on. There are not many sufficient solutions in the research field regarding the provisioning of resources in fog computing. Thus, this paper reviews various methods established for resource provisioning in fog computing using different parameters from 2015 to 2021 and presents the limitations, advantages, and future directions to various resource provisioning techniques in fog computing.